Bone mineral density in healthy Syrian women measured by dual energyX-ray absorptiometry - Bakir, Mohamed Adel; Hammad, Kholoud B; Habil, Khuzama M (Anthropological Review, 2018)
Assessment of bone mineral density (BMD) using dual energy X-ray absorptiometry (DXA) technique is considered as a standard technique for diagnosing osteopenia and osteoporosis and evaluating the severity of such diseases. Numerous studies have demonstrated the necessity to establish an ethnicspecific reference data for Bone mineral density measurements. Such data are lacking for the Syrian population. The objectives of this study are (1) to establish BMD reference values in a group of healthy Syrian women using DXA technique, (2) to compare with values from other populations, (3) to study the prevalence of osteopenia and osteoporosis in Syrian women using the manufacturer reference values. A total of 951 healthy Syrian women aged 20-79 years participated in this study. Weight, height, and BMI have been determined. BMD measurements were performed using Lunar Prodigy Advance System (GE).The data were compared with those from other populations. The results have demonstrated the expected decline in BMD with age after peaking at 30-39 years old group. The peak values of the lumbar spine and femur neck were 1.16 (0.12), and 0.95 (0.13) g/cm2, respectively. The results of the Syrian women were compared with those from other populations and the differences were presented. Osteopenia was diagnosed in 35.80% and 60.31% and osteoporosis in 6.23% and 2.72% in lumbar spine and femur neck, respectively, of women 50-59 years of age. These ratios increased to 36.84%, 68.42% and 23.68%, 13.10%, respectively, in the age group more than 59 years. BMD values of the Syrian women were determined for the first time. The results demonstrate the importance of establishing population-specific reference range for BMD values for an accurate assessment of Osteoporosis. High prevalence of osteopenia and osteoporosis was demonstrated in Syrian using the manufacturer reference values.